Perspective on distributed direct air capture: what, why, and how? - Yuanke Chen; Ronghui Wu; Po-Chun Hsu (npj Materials Sustainability)
Abstract Direct air capture (DAC) is widely considered as a critical negative emission technology to not only mitigate but reverse global climate change. While commercially expanding, its efficiency is limited by energy-intensive sorbent regeneration. Here, we highlight distributed DAC as a complement to centralized systems, analyzing the regeneration energy demands and carbon footprints of various sorbents. A comprehensive evaluation of distributed DAC’s impact is crucial for maximizing its potential.